Bank of Canada communication, media coverage, and financial market reactions - Bernd Hayo; Matthias Neuenkirch (Philipps-University Marburg, Faculty of Business Administration and Economics, 2010)
We examine the impact of Bank of Canada communications and media reporting on them on Canadian (short- and medium-term) bond and stock market returns using a GARCH model. Communications are rather uniformly distributed over the sample period (1998-2006); however, media coverage is particularly high during phases of increased uncertainty about the future course and timing of Canadian monetary policy. Official communications exert a larger influence on the bond market, whereas media coverage is more relevant for the stock market. In general, media filtering does not play a prominent role.
Keywords: E52; G14; G15; 330; Bank of Canada; central bank communication; financial markets; media coverage; monetary policy; Geldpolitik; Staatliche Information; Mediale Berichterstattung; Wirkungsanalyse; Börsenkurs; Kapitalertrag; Finanzmarkt; Kanada